Interoceptive conditioning in rats: Effects of using a single training dose or a set of 5 different doses of nicotine - Pittenger, Steven T. (2013)
Interoceptive conditioning contributes to the tenacity of nicotine dependence. Previous research investigating nicotine as an interoceptive stimulus has typically employed administration of a single training dose of nicotine over an extended time. This approach has allowed for careful study of the nicotine stimulus. In humans, the nicotine stimulus is unlikely to be fixed across learning episodes. Thus, from a translational perspective, systematic variation of nicotine dose in training might better approximate interoceptive conditioning in humans. Notably, training with a class or set of discrete exteroceptive stimuli (e.g., different pictures of cars) produces interesting behavioral differences relative to training with a single stimulus. The present study sought to determine whether similar differences would occur if a set of nicotine stimuli were used in place of a single dose. To investigate this question, one group of male Sprague-Dawley rats was trained on a discriminated goal-tracking task with a set of nicotine doses (0.05, 0.125, 0.2, 0.275, and 0.35 mg/kg). A second group received the standard protocol of training with a single nicotine dose (0.2 mg/kg). On each nicotine session, there was intermittent access to liquid sucrose (26%) in a conditioning chamber. On intermixed saline sessions, sucrose was withheld. We examined acquisition, subsequent extinction, transfer of extinction, nicotine generalization, and mecamylamine blockade. Both groups reliably discriminated between nicotine and saline sessions, were sensitive to non-reinforcement, displayed transfer of extinction, demonstrated dose-dependent nicotine generalization, and responding was blocked by mecamylamine. There were no significant differences between the two groups. The unique nature of an interoceptive pharmacological stimulus and the challenges posed for studying the impact of training with a set of interoceptive stimuli are discussed.